2020
DOI: 10.1149/2162-8777/abb8bc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Viscosity on Ceria Abrasive Removal during the Buff Clean Process

Abstract: In this study, the effect of viscosity on ceria abrasive removal during the buff clean process was investigated. First, a numerical simulation was performed to observe the shear stress on the wafer. The shear stress increased as the viscosity increased. These results imply that the viscosity increases the drag force acting on the abrasives, which can improve abrasive removal. Based on the results of the numerical simulation, the ceria abrasive removal was measured using inductively coupled plasma mass spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It has been reported that in a water buff clean process, most of the ceria particles can be removed. 12,20 After the buff clean with DIW only, Fig. 2b shows that the number of the residual ceria particles on the SiO 2 surface reduces to 361.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in a water buff clean process, most of the ceria particles can be removed. 12,20 After the buff clean with DIW only, Fig. 2b shows that the number of the residual ceria particles on the SiO 2 surface reduces to 361.…”
Section: Resultsmentioning
confidence: 99%
“…19 Kim et al showed that the buff clean process with DIW could remove most of the residual ceria particles and adding glycerol to DIW could improve the CE of ceria particles because of the increased viscosity of the cleaning solution. 20 There have been some studies on the use of additives (complexing agents and surfactants) to improve the effectiveness of ceria particles removal and reduce the use of chemicals in post-CMP cleaning. However, the removal of ceria particles from the SiO 2 substrates using surfactants in the buff clean step has not been systematically studied.…”
mentioning
confidence: 99%
“…17,18 Smaller ceria particles with a high concentration of Ce 3+ species on the surface 19 have a strong affinity towards the oxide surface and, hence, a higher oxide removal rate. At the same time, since these particles form strong Ce-O-Si bonds with the oxide surface, it is very difficult to remove them 20,21 as shown recently by several authors who evaluated the effectiveness of different cleaning chemistries 22,23 and techniques 24,25 to clean them. These studies make it clear that the post-CMP cleaning process should be capable not only of dislodging these particles from the substrate but also, as stated above, preventing their subsequent redeposition on the substrate.…”
mentioning
confidence: 99%
“…3 These contaminants can cause circuit defects on the wafer, 4 and various cleaning methods have been suggested to improve post-CMP cleaning. [5][6][7] Recently, it has been reported that small ceria particles remaining on the silicon dioxide wafer are difficult to remove after polishing. 8,9 In addition, problems with agglomeration of slurry particles by shear-induced which can affect to slurry stability have been reported in the CMP process.…”
mentioning
confidence: 99%